Sodium Hyaluronate Eye Drops for College Students with Computer Vision Syndrome in Indonesia - Zulkarnain, Bambang Subakti; Loebis, Rozalina; Aryani, Toetik (Folia Medica Indonesiana, 2022)
Highlights: • Computer vision syndrome (CVS) that causes dry eyes becomes a health problem for college students. • Sodium hyaluronate eyedrops can be used as one of the CVS therapy strategies for students suffering from CVS. Abstract: The use of computers and mobile devices is increasing. Computers and mobile devices help our daily work or study. However, prolonged use of them may cause computer vision syndrome (CVS). Nowadays, CVS becomes a health problem for everyone working with computers or mobile devices including college students because it causes dry eyes. It may disrupt reading, doing professional work, or using a computer which is important for college students to complete academic tasks. Sodium hyaluronate can be used to overcome the dry eye problem due to CVS. To assess the effectiveness of sodium hyaluronate eyedrops on students suffering from CVS, pre- and post-administration of sodium hyaluronate was measured for two weeks. Inclusion criteria for this study were college students aged 20-35 years, using a computer for >2 hours a day, not using nonsteroidal anti-inflammatory drugs (NSAIDs), not consuming drugs, or having a disease that affects tear production and bearing no pregnancy. Parameters assessed include tear break-up time using the Tear Break-Up Time (TBUT) test, tear production using the Schirmer I test, the number of clinically subjective symptoms, and Ocular Surface Disease Index (OSDI) scores. Data were analyzed using student paired t-tests or Wilcoxon Rank Test. There were statistically significant differences before and after the TBUT (4.4 vs 6.7 seconds; p<0.0001); the Schirmer I Test (4 vs 6 mm; p<0.05), and the number of clinically subjective symptoms (3 vs 0 clinically subjective symptoms; p<0.0001). The OSDI scores did not show statistical differences before and after administration of sodium hyaluronate (27 vs 21; p>0.05), but there was a positive impact from moderate to mild dry eye. Sodium hyaluronate eyedrops can be used as one of the CVS therapy strategies for students suffering from CVS.